Binalebu-3: A high yielding, year-round, scented and seedless variety of lemon - Alam, M S; Islam, M R (Bangladesh Journal of Nuclear Agriculture, 2025)
An investigation was carried out in three consecutive years at the Horticulture Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh to characterize lemon germplasm for varietal development. Thirty-one local and exotic lemon germplasm were collected from home and abroad. The germplasm CL-0021 and CL-0027 were collected from Darziling, India. These two germplasm alone with check variety were evaluated during 2017-18, 2018-19 and 2019-20 at two location viz.Kashiar char, Mymensingh and Garobazar, Madhupur, Tangail. The experiments were carried out following randomized complete block design with three replications. BAUlebu-4 was used as a check variety in the experiments. From the results it was observed that CL-0021 was found to be superior to other exotic genotype and check variety BAUlebu-4 in case of fruit setting, disease and disease resistant. During 2017-18, 2018-19 & 2019-20 at Mymensingh, the highest fruit yield plant-1(55.50, 42.23 kg and 33.01 kg respectively), vitamin C (88.15, 88.21and 88.14 mg 100 g-1), plant height (225.55 cm, 189.11 cm and 165.01 cm), fruit length (7.92, 7.71 cm and 7.69 cm), number of fruits plant-1 (250.00, 2014.24 and 150.00), juice content fruit-1 (48.00%, 46.22% and 44.74%) and the lowest number of seeds fruit-1 (4.2,4.1, and 4) was recorded from CL-0021 in all the three consecutive year trials. Similar results were also observed at another location, Garobazar, Madhupur, which was higher compared to CL-0027 and BAUlebu-4 at both locations. The lowest fruit yield plant-1, vitamin C, the highest number of seeds fruit-1 observed at CL-0027 at both of Mymensingh and Tangail. Considering the better performance of fruit yield, vitamin C content, juice content and less number of seeds compare to CL-0021, CL-0027 and BAUlebu-4; CL-0021 genotype was selected as a new variety naming Binalebu-3 to grow commercially all over Bangladesh. Bangladesh J. Nuclear Agric, 38(2): 27-34, 2024